2018
DOI: 10.1109/tuffc.2017.2719962
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Spectral Log Difference Technique for Ultrasonic Attenuation Imaging

Abstract: The attenuation coefficient slope (ACS) has the potential to be used for tissue characterization and as a diagnostic ultrasound tool, hence complementing B-mode images. The ACS can be valuable for the estimation of other ultrasound parameters such as the backscatter coefficient. There is a well-known tradeoff between the precision of the estimated ACS values and the data block size used in the spectral-based techniques such as the spectral-log difference (SLD). This tradeoff limits the practical usefulness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…Thus, these parameters can be considered piecewise continuous. [19] This condition can be used to improve parameter estimation. Similar to our previous work in the field of elastography [24], [21], we proposed a regularized cost function that incorporates both data terms and prior information for parameter estimation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these parameters can be considered piecewise continuous. [19] This condition can be used to improve parameter estimation. Similar to our previous work in the field of elastography [24], [21], we proposed a regularized cost function that incorporates both data terms and prior information for parameter estimation.…”
Section: Methodsmentioning
confidence: 99%
“…Although this method substantially improved the results compared to the commonly used Reference Phantom Method (RPM) [17], it calculates these parameters at each spatial location independent of its neighbors and hence neglects spatial dependency of these coefficients. More recently, Coila et al [18], [19] adapted the conventional spectral log difference technique for attenuation estimation by adding a regularization term. Despite substantially improving the results, this work only estimates attenuation (not backscattering).…”
Section: Introductionmentioning
confidence: 99%
“…These works are commonly addressed as tissue characterization or quantitative US. Most of them are based on the estimation of statistical or spectralbased parameters from image regions extracted from different tissues (e.g., [1]) or on the estimation of acoustic parameter maps such as the attenuation coefficient (e.g., [2]).…”
Section: Introductionmentioning
confidence: 99%
“…Such quantitative measurements, very useful in computer-aided screening tools, are generally extracted from US images such as beamformed radiofrequency (RF), envelope, computed by demodulation of individual RF signal, or B-mode, log-compressed envelope, images. The most used parameters to characterize the tissues rely on acoustical properties (e.g., attenuation, speed of sound, backscattering coefficient [1]) or statistical and spectral information (e.g., [2]). In addition, several studies showed the interest of extracting from US images fractal or multifractal parameters, potentially related to the fractal or multifractal behavior of tissues in space and time (e.g., [3]).…”
Section: Introductionmentioning
confidence: 99%